Association of gastroesophageal reflux disease with increased risk of chronic otitis media with effusion in adults: A nationwide population-based cohort study. Issue 33 (20th August 2021) - Yeo, Cha Dong; Kim, Jong Seung; Lee, Eun Jung
Abstract : Abstract: This study aimed to evaluate the risk of developing chronic otitis media with effusion (OME) in individuals with gastroesophageal reflux disease (GERD). A retrospective propensity score-matched cohort study was performed using data from the Korea National Health Insurance Service. The GERD group (n = 3532) included certain individuals who had been diagnosed with GERD between January 2002 and December 2005. A comparison control group (n = 14, 128) was calculated by 1:4 propensity score matching considering age, sex, and comorbidities and year of enrollment. Each patient was monitored until 2013. Survival analysis, the Log-rank test, and Cox proportional hazard regression models were used to calculate the incidence, survival rate, and hazard ratio (HR) of chronic OME for each group. Among the 17, 660 individuals included in the study population (53.2% men), the overall incidence of chronic OME during the 11-year follow-up was 1.84-fold higher in the GERD group than in the non-GERD group (1.8 vs 3.0 per 1000 person-year; adjusted HR 1.84; 95% confidence interval [CI], 1.46–2.31). Moreover, the adjusted HRs of developing chronic OME (allergic rhinitis, 1.69 [95% CI, 1.37–2.10]; asthma, 1.29 [95% CI, 1.02–1.64]; chronic rhinosinusitis, 1.61 [95% CI, 1.26–2.05]) were greater in study population with comorbidities. From long-term follow-up, the prevalence of chronic OME in adults was 1.84 times higher in the GERD group compared with the non-GERD group. Specifically, it found that allergic rhinitis, asthma, or chronic rhinosinusitis showed increase the risk of developing chronic OME than those without these conditions.